Engram reactivation during memory retrieval predicts long-term memory performance in aged mice - Gülmez Karaca, Kübra; Brito, David V. C.; Kupke, Janina; Zeuch, Benjamin; Oliveira, Ana (Neurobiology of aging, 2021)
Age-related cognitive decline preferentially targets long-lasting episodic memories that require intact hippocampal function. Memory traces (or engrams) are believed to be encoded within the neurons activated during learning (neuronal ensembles), and recalled by reactivation of the same population. However, whether engram reactivation dictates memory performance late in life is not known. Here, we labeled neuronal ensembles formed during object location recognition learning in the dentate gyrus, and analyzed the reactivation of this population during long-term memory recall in young adult, cognitively impaired- and unimpaired-aged mice. We found that reactivation of memory-encoding neuronal ensembles at long-term memory recall was disrupted in impaired but not unimpaired-aged mice. Furthermore, we showed that the memory performance in the aged population correlated with the degree of engram reactivation at long-term memory recall. Overall, our data implicates recall-induced engram reactivation as a prediction factor of memory performance in aging. Moreover, our findings suggest impairments in neuronal ensemble stabilization and/or reactivation as an underlying mechanism in age-dependent cognitive decline.
Gesehen am 17.06.2021